2021
DOI: 10.1007/s11252-021-01113-7
|View full text |Cite
|
Sign up to set email alerts
|

Urban ecosystem services in strategic planning in Swedish municipalities

Abstract: Research to date on urban ecosystem services has mainly been conducted in large cities, particularly in China, the USA and some European countries. This study examined the provision of urban ecosystem services in a Swedish municipality context, based on interviews with municipal stakeholders in strategic management and planning from six municipalities and a review of existing publications readily available to practitioners. The analysis focused on (1) the ecosystem services explicitly covered, (2) whether mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…The ability of UGI to provide regulating ES was deemed of central importance for the future of all three cities. This corroborates many existing studies in which regulating ES are receiving high attention within urban planning (e.g., Cortinovis and Geneletti, 2018;Sang et al, 2021) amid popularity of NbS and ecosystem-based adaptations to address the associated challenges (e.g., Brink et al, 2016;Geneletti and Zardo, 2016;Seddon et al, 2020). At the same time, our study made clear the importance of different cultural, provisioning and supporting ES in all three cities.…”
Section: Stakeholder Priorities and Apparent Urgency For Essupporting
confidence: 90%
See 1 more Smart Citation
“…The ability of UGI to provide regulating ES was deemed of central importance for the future of all three cities. This corroborates many existing studies in which regulating ES are receiving high attention within urban planning (e.g., Cortinovis and Geneletti, 2018;Sang et al, 2021) amid popularity of NbS and ecosystem-based adaptations to address the associated challenges (e.g., Brink et al, 2016;Geneletti and Zardo, 2016;Seddon et al, 2020). At the same time, our study made clear the importance of different cultural, provisioning and supporting ES in all three cities.…”
Section: Stakeholder Priorities and Apparent Urgency For Essupporting
confidence: 90%
“…The structural pressures that many cities are experiencing has led to attempts to maximize the efficiency of UGI, and thus rely on compact multifunctional UGI to deliver and accommodate more services in increasingly smaller spaces. This aligns with results from Sang et al (2021) who found that Swedish municipal planners saw the potential for multifunctional UGI combining regulating, supporting and cultural ES. This was particularly the case where specific problems needed to be solved, resulting in negotiation on a project-by-project basis.…”
Section: Common Rationales For Ugisupporting
confidence: 89%
“…We outline what plant functional traits specifically have been used to identify relationships with ES provision and discuss the theoretical and quantitative evidence these traits might hold as indicators. ES are increasingly relevant for both researchers and policymakers alike, and knowledge of functional traits as measures of ES could be incorporated into estimates of natural resources and capital for municipalities (Lam & Conway, 2018; Sang et al, 2021), conservation and restoration (do Vale et al, 2010; Zirbel et al, 2017), and measures of changes in ecosystems due to climate change and urban expansion (Song et al, 2019). The objectives of this paper are to (a) offer a current review of the literature on ecosystem service–plant functional trait relationships, (b) identify which traits have been used to successfully indicate ecosystem services, and which traits have strong theoretical evidence, and (c) identify research gaps, and ecosystem services or traits that receive little attention or have weak criteria as indicators.…”
Section: Introductionmentioning
confidence: 99%
“…A well-functioning ecosystem provides various services ( Chien, 2022 ; Jaung et al., 2022 ). In urban areas, ecosystem services components are broadly divided into two parts; the green ecosystem components and the blue ecosystem components ( Caro-Borrero and Carmona-Jiménez 2019 ; Hagemann et al., 2020 ; Mukherjee and Shaw 2021 ; Sang et al., 2021 ). The green components include all sorts of green infrastructures and the blue components include all sorts of natural water structures/systems ( Caro-Borrero and Carmona-Jiménez 2019 ; Kazmierczak and Carter 2010 ).).…”
Section: Introductionmentioning
confidence: 99%
“…More generally, the nature-based solution is a term that can be used to describe an alternative and non-traditional approaches to environmental issues, like flooding, water scarcity, or soil erosion, by harnessing natural capital ( Haase 2017 ; Chen et al., 2022 ). They also provide a wide range of other important benefits, such as cleaner air and water, economic benefits, and increased biodiversity ( Amini et al., 2019 ; Hagemann et al., 2020 ; Sang et al., 2021 ). Nature-based solutions span a wide range of practices, and people sometimes disagree about exactly what counts as a nature-based solution.…”
Section: Introductionmentioning
confidence: 99%